Percutaneous full-endoscopic uniportal decompression for the treatment of symptomatic idiopathic lumbar spinal epidural lipomatosis: Technical note - Yong Yu; Ye Jiang; Fulin Xu; Lutao Yuan; Yuhang Mao; Chen Li (Frontiers in Surgery, 2022)
BackgroundLumbar spinal epidural lipomatosis (SEL) is a rare condition characterized by an excessive accumulation of adipose tissue within the spinal canal, compressing the dura sac and/or nerve roots. When conservative treatments fail and clinical symptoms progress quickly and seriously, surgical decompression should be considered. With the rapid development of endoscopic armamentaria and techniques, the pathological scope that can be treated by percutaneous endoscopic spine surgery is ever expanding.ObjectiveIn this paper, the authors describe a patient with lumbar spinal epidural lipomatosis who was treated with a percutaneous full-endoscopic uniportal decompression surgery successfully. This article aims to validate the feasibility of percutaneous full-endoscopic uniportal decompression for the treatment of symptomatic idiopathic spinal epidural lipomatosis via interlaminar approach.MethodsWe describe a case of a 69-year-old man with a 10-year history of low back pain, intermittent claudication, and bilateral leg neuropathic pain. He was diagnosed with lumbar epidural lipomatosis, which did not respond to conservative therapy. After a comprehensive evaluation, he underwent percutaneous endoscopic spine surgery to remove hyperplastic adipose tissue and decompress nerve roots and dura sac.ResultsThe patient was treated with a percutaneous full-endoscopic uniportal decompression surgery successfully. After the procedure, his leg pain decreased and his walking capacity improved. There were no surgery-related complications, such as cerebrospinal fluid leakage, incision infection, etc.ConclusionsThe case with SEL was successfully treated with a percutaneous full-endoscopic uniportal surgery, which has the advantages of excellent presentation of anatomical structures, expanded field of vision, less surgical-related trauma, and bleeding. The key point of the procedure is to release and cut off the bands which divide the epidural space into small rooms filled with excess adipose tissue.